Impacts of thermo-physical properties of gas and liquid phases on design of absorber for CO2 capture using monoethanolamine. (September 2016) - Nookuea, Worrada; Tan, Yuting; Li, Hailong; Thorin, Eva; Yan, Jinyue
Highlights: The property impacts of the CO2 mixtures on the designs of the packed bed absorber were analyzed. The property impacts of the CO2 mixtures on the capital cost of the absorption unit were evaluated. The priority for the property model development was identified. Abstract: Absorption of CO2 with aqueous amines in post-combustion capture is characterized as a heat and mass transfer processes with chemical reaction, which is sensitively affected by the thermo-physical properties of fluids. In order to optimize the design of the absorber of CO2 capture process, in this paper, the impacts of thermo-physical properties on the column design were investigated. Furthermore, the property impacts on the capital cost of the absorber unit were also identified and analyzed. Results show that the gas phase density has the most significant effect on the column diameter. Underestimation of the gas phase density of 10% may result in an increase of about 6% of the column diameter. For the packing height, the liquid phase density has the most significant effect. 10% underestimation of the liquid phase density may result in an increase of 8% of the packing height. Moreover, the effect from the liquid phase viscosity is also significant. For the annual capital cost, the liquid phase density also shows the most significant effect. Underestimation of the liquid phase density of 10% leads to the cost overestimation of $1.4 million for the absorption column for a 400 MW coal-fired power plant. Therefore, the development of the flue gas density model and liquid phase density and viscosity models of the aqueous amine solution with CO2 loading should be prioritized.